PROSES KREATIF KOMUNITAS TEATER SENDRATASIK UNIVERSITAS NEGERI SURABAYA DIMASA PANDEMI COVID-19 - Keling, Carolina (APRON Jurnal Pemikiran Seni Pertunjukan, 2023)
The creative process is the effort of a person or group in creating new creativity in order to solve a problem that occurs at a certain time. In this study, the creative process that became the discussion was the process carried out by the Sendratasik Theatre Community, Faculty of Language and Arts of Surabaya State University. The uniqueness of the creative process that occurs in the Sendratasik Theater Community is the continuity of the program that continues to be carried out during the Covid-19 pandemic by taking into account existing restrictions, but achievement remains the main goal. So with this uniqueness, the formulation of the problem arises in the form of 1) how is the creative process of the Sendratasik Theatre Community during the COVID-19 pandemic? 2) How is the implementation of the creative process of the Teater Sendratasik community during the COVID-19 pandemic? Thus the research method used by researchers is a descriptive qualitative research method. So that the data obtained is in the form of words or descriptions obtained through observation, interviews, and documentation. The results showed that the creative process carried out by the theater community during the Covid-19 period was by considering the theory revealed by Bobbi Deporter and Mike Hernacki in a book entitled Quantum Lerning (Alwiyah, 2007: 301) and carrying out 5 stages of the creative process including 1) preparation, 2) incubation, 3) illumination, 4) verification, 5) application. So by doin these 5 stages, it can be concluded that the Teater Sendratasik community carries out a hybrid creative process. For example, the production of ARTEFAC in 2022 with the script Please by Nano Riantiarno. Keywords : Creative process, Community, Theatre, Covid-19.